Caracterización fenotípica y molecular de especies silvestres de solanum con resistencia cuantitativa al tizón tardio - Gonzales, E. (Universidad Nacional Agraria la Molina, 2003)
Late blight caused by the oomycetous pathogen Phytophthora infestans (Mont.) de Bary is the most important disease of potato crop worldwide. The use of wild species as source of resistance in plant breeding programs has become a great alternative for the control of the disease. In order to identify sources of quantitative resistance among wild Solanum species, 9 species (S. bukasovii, S. bulbocastanum, S. chomatophilum, S. capsicibaccatum, S. megistacrolobum, S. microdontum, S. raphanifolium, S. tarijense and S. verrucosum) were characterized for resistance to late blight in detached leaf assays, greenhouse and field experiments. Six of the selected species showed most of the genotypes free of R-genes, suggesting quantitative resistance to late blight. To identify the genes associated to quantitative resistance, two of these species ( S. megistacrolobum and S. raphanifolium) were characterized with molecular markers. The individuals of each species were grouped according to their phenotypic response in greenhouse in resistant or susceptible. These groups were then analyzed molecularly using ligation mediated polymerase chain reaction with primers obtained from genes involved in plant defense reactions. During this stage, new primers corresponding to genes that are suspected to have a role in plant defense were also designed. Then, the frequency of bands associated with each phenotypic group was tested using x2-test. Finally, some of the bands found significantly associated with one of the phenotypic categories were cloned and sequenced to verify if they correspond to candidate genes of the defense response.